Posterior Cruciate Ligament Graft Fixation Angles, Part 1: Biomechanical Evaluation for Anatomic Single-Bundle Reconstruction. (October 2014) - Kennedy, Nicholas I.; LaPrade, Robert F.; Goldsmith, Mary T.; Faucett, Scott C.; Rasmussen, Matthew T.; Coatney, Garrett A.; Engebretsen, Lars; Wijdicks, Coen A.
Background: Currently, no consensus exists for the optimal graft fixation angle for anatomic single-bundle (SB) posterior cruciate ligament reconstructions (PCLRs). Additionally, direct graft forces have not been measured. Alternative graft fixation angles and the resultant graft forces should be investigated to optimize the stability of SB PCLRs without overconstraining the knee. Hypothesis: Graft fixation angles of 75°, 90°, and 105° for SB PCLR were hypothesized to improve knee stability compared with the sectioned posterior cruciate ligament state with no evidence of knee overconstraint. Study Design: Controlled laboratory study. Methods: Nine fresh-frozen human cadaveric knees were biomechanically evaluated for the intact, sectioned, and SB PCLR states with the anterolateral bundle graft fixed at 75°, 90°, and 105°. A 6 degrees of freedom robotic system assessed knee laxity with a 134-N posterior load applied at 0° to 120° and 5-N·m external, 5-N·m internal, and 10-N·m valgus rotation torques applied at 60° to 120°. By securing the graft to an external load cell, graft forces were measured throughout kinematic testing. Results: No significant kinematic differences were found among the 3 fixation angles. Each fixation angle resulted in significantly less posterior translation than in the sectioned state at all flexion angles ( P < .05), with 4.1 mm of average residual laxity during an applied posterior loading. For all graft fixation angles, internal rotation was significantly increased between 60° and 120° of flexion, and external rotation was significantly increased at 90°, 105°, and 120° of flexion compared with the intact state. Graft forces were not significantly different among the 3 fixation angles and remained below reported loads observed during activities of daily living. Conclusion: All tested SB PCLR graft fixation angles restored knee laxity to similar levels; however, persistent laxity resulted in significant increases in knee laxity compared with the intact state during posterior tibial loading at all flexion angles, internal rotation at flexion angles ≥60°, and external rotation at ≥75° of flexion. Clinical Relevance: The results of this study suggest that SB PCL graft fixation angles of 75°, 90°, and 105° were comparable in restoring knee kinematics and exposed the graft to similar time-zero loads. However, SB PCLRs did not fully reduce knee laxity to the intact state.